Effects of strength training using unstable surfaces on strength, power and balance performance across the lifespan: A systematic review and meta-analysis - Behm, D. G.; Muehlbauer, T.; Kibele, A.; Granacher, U. (Sports Medicine, 2015)
Background: The effectiveness of strength training on unstable surfaces (STU) versus stable surfaces (STS) or a control condition (CON; i.e. no training or regular training only) for strength, power and balance performance across the lifespan has not yet been investigated in a systematic review and meta-analysis.